Rancang Bangun Generator HHO untuk Aplikasi pada Engine 1108 Cm3 - Rino Sukma; Nofriyandi Nofriyandi; Hanif Hanif; Dian Wahyu; Andriyanto Andriyanto (METAL: Jurnal Sistem Mekanik dan Termal, 2020)
Electrolysis is a method used to describe the composition of air. electrolysis converts air bonds (H2O) into its constituent compounds flammable Hydrogen and Oksigen which help the combustion process. Water electrolytic devices are called HHO generators, HHO generators use pure water electrolysis, the results of the meeting between H2 and O2 will be used as alternative fuels in meeting renewable energy needs. This research uses a HHO generator. Testing the performance of the HHO generator is done experimentally on a laboratory scale. The first stage is making a dry type HHO generator using SS316L plate. The size of the plate is 70 mm x 70 mm, the center of the plate is punched Ø 12 mm, the top and the bottom of the plate are perforated Ø 10 mm. The HHO generator consists of  5 cells and 4 neutral plates for each cell by agreeing 5, 7 and 9 grams of KOH for 1 liter of distilled water. The results of the production of HHO gas produces a large amount of H2 and O2 which flows in units of minutes at a volume of 500 ml. HHO gas production parameters will depend on current, power and efficiency will increase from each of the above variables. Measurements use special measurement tools to distinguish which are quite significant